2016
DOI: 10.1063/1.4956439
|View full text |Cite
|
Sign up to set email alerts
|

Direct gap Ge1-ySny alloys: Fabrication and design of mid-IR photodiodes

Abstract: Chemical vapor deposition methods were developed, using stoichiometric reactions of specialty Ge3H8 and SnD4 hydrides, to fabricate Ge1-ySny photodiodes with very high Sn concentrations in the 12%–16% range. A unique aspect of this approach is the compatible reactivity of the compounds at ultra-low temperatures, allowing efficient control and systematic tuning of the alloy composition beyond the direct gap threshold. This crucial property allows the formation of thick supersaturated layers with device-quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…1 Attempts to circumvent the quality issues to achieve alloys with y >> 0.15 are based on lowering the growth temperature to about 150 ℃, [2][3][4][5] or using complex buffer layers with intermediate compositions. [6][7][8] However, very few reports have been published on band gaps from such samples, 4,8,9 and the few results available are difficult to compare due to unknown or large strains present, compositional uncertainties, different methodologies for extracting the band gaps, and sample complexity. In this letter, we report on the structural and optical characterization of a series of Ge1-ySny alloys that meet three criteria that reduce the band gap uncertainty and simplify the analysis of optical experiments: first, a smooth and monotonic compositional dependence of the structural properties that is consistent with previous measurements of low-Sn alloys with proven quality; second, small levels of strain that minimize errors associated with deformation potentials and elastic parameters 10 (and their unknown compositional dependence); and third, elimination of buffer layers that make it difficult to extract the optical properties of the Ge1-ySny layer of interest.…”
mentioning
confidence: 99%
“…1 Attempts to circumvent the quality issues to achieve alloys with y >> 0.15 are based on lowering the growth temperature to about 150 ℃, [2][3][4][5] or using complex buffer layers with intermediate compositions. [6][7][8] However, very few reports have been published on band gaps from such samples, 4,8,9 and the few results available are difficult to compare due to unknown or large strains present, compositional uncertainties, different methodologies for extracting the band gaps, and sample complexity. In this letter, we report on the structural and optical characterization of a series of Ge1-ySny alloys that meet three criteria that reduce the band gap uncertainty and simplify the analysis of optical experiments: first, a smooth and monotonic compositional dependence of the structural properties that is consistent with previous measurements of low-Sn alloys with proven quality; second, small levels of strain that minimize errors associated with deformation potentials and elastic parameters 10 (and their unknown compositional dependence); and third, elimination of buffer layers that make it difficult to extract the optical properties of the Ge1-ySny layer of interest.…”
mentioning
confidence: 99%
“…Such detectors, therefore, only operate under cooled conditions, typically between 4 and 78 K. Here, we show that hyperdoped Ge:Au has fundamentally different properties from those of conventional Ge:Au, namely, a much larger sub-band-gap absorption coefficient comparable to that of direct-band-gap semiconductors and room temperature sub-band-gap SWIR photodetection [38]. We note that significant progress has been made on Ge-Sn alloys [39,40], which have recently demonstrated room-temperature SWIR photodetection [41][42][43][44] and lasing [21,45], but which operate by a fundamentally different sub-bandgap absorption mechanism than that of the Au-dopant mediation investigated here. Ge-Sn alloying (∼+9 % Sn) creates high compressive strain, which can induce a redshifted direct-band-gap transition [39,40].…”
Section: Introductionmentioning
confidence: 77%
“…Mathews et al demonstrated the first photodetectors made from Ge-Sn alloys, and detectors with 2% Sn were shown to cover the entire telecommunications spectrum [49]. Since then, photodetectors with Sn content up to 16% have been achieved using this method [50,51]. The CVD approach using SnD 4 also lead to the first observable luminescence from Ge-Sn alloys.…”
Section: Ge-sn Alloy As An Intrinsically Direct Band Gap Materialsmentioning
confidence: 99%